Adults' past-day recall of sedentary time: Reliability, validity, and responsiveness - Clark, B.; Winkler, E.; Healy, Genevieve; Gardiner, P.; Dunstan, D.; Owen, N.; Reeves, M. (2013)
Purpose: Past-day recall rather than recall of past week or a usual/typical day may improve the validity of self-reported sedentary time measures. This study examined the test–retest reliability, criterion validity, and responsiveness of the seven-item questionnaire, Past-day Adults’ Sedentary Time (PAST). Methods: Participants (breast cancer survivors, n = 90, age = 33–75 yr, body mass index = 25–40 kg·m−2) in a 6-month randomized controlled trial of a lifestyle-based weight loss intervention completed the interviewer-administered PAST questionnaire about time spent sitting/lying on the previous day for work, transport, television viewing, nonwork computer use, reading, hobbies, and other purposes (summed for total sedentary time). The instrument was administered at baseline, 7 d later for test–retest reliability (n = 86), and at follow-up. ActivPAL3-assessed sit/lie time in bouts of ≥5 min during waking hours on the recall day was used as the validity criterion measure at both baseline (n = 72) and follow-up (n = 68). Analyses included intraclass correlation coefficients, Pearson’s correlations (r), and Bland–Altman plots and responsiveness index.Results: The PAST had fair to good test–retest reliability (intraclass correlation coefficient = 0.50, 95% confidence interval [CI] = 0.32–0.64). At baseline, the correlation between PAST and activPAL sit/lie time was r = 0.57 (95% CI = 0.39–0.71). The mean difference between PAST at baseline and retest was −25 min (5.2%), 95% limits of agreement = −5.9 to 5.0 h, and the activPAL sit/lie time was −9 min (1.8%), 95% limits of agreement = −4.9 to 4.6 h. The PAST showed small but significant responsiveness (−0.44, 95% CI = −0.92 to −0.04); responsiveness of activPAL sit/lie time was not significant. Conclusion: The PAST questionnaire provided an easy-to-administer measure of sedentary time in this sample. Validity and reliability findings compare favorably with other sedentary time questionnaires. Past-day recall of sedentary time shows promise for use in future health behavior, epidemiological, and population surveillance studies.